Penicillin-G dimethylamide - G. Chass, Queen Mary University of London (My University, 2013)
Inelastic Neutron Scattering spectrum of Penicillin-G dimethylamide, C₁₈H₂₃N₃O₃S, measured on the TOSCA instrument. Benzylpenicillin sodium salt.
Keywords: TOSCA